2019
DOI: 10.1002/mbo3.789
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the microbiota in gastrointestinal tract segments of Rhabdophis subminiatus: Dynamic changes and functional predictions

Abstract: The gut microbiota helps the host to absorb nutrients and generate immune responses that can affect host behavior, development, reproduction, and overall health. However, in most of the previous studies, microbiota was sampled mainly using feces and intestinal contents from mammals but not from wild reptiles. Here, we described the bacterial profile from five different gastrointestinal tract (GIT) segments (esophagus, stomach, small intestine, large intestine, and cloaca) of three wild Rhabdophis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 57 publications
13
32
0
Order By: Relevance
“…In addition, three mucosa sites had no significant differences in terms of microbial diversity and displayed a lower microbial diversity compared with the digesta. Our results were consistent with those in previous studies, in that no significant differences in microbial diversity were found at different fish gastrointestinal mucosa sites [ 34 , 39 ]. Moreover, results from other studies showed that several fish had significantly lower richness and diversity for the gastrointestinal mucosa-associated microbiota compared with the digesta-associated microbiota [ 34 , 40 ], which was consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, three mucosa sites had no significant differences in terms of microbial diversity and displayed a lower microbial diversity compared with the digesta. Our results were consistent with those in previous studies, in that no significant differences in microbial diversity were found at different fish gastrointestinal mucosa sites [ 34 , 39 ]. Moreover, results from other studies showed that several fish had significantly lower richness and diversity for the gastrointestinal mucosa-associated microbiota compared with the digesta-associated microbiota [ 34 , 40 ], which was consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…This divergence was likely due to differences in the lake’s natural water and farmed water environments, as well as fish food sources. Regarding the digesta, the stomach contents displayed a significantly higher microbial diversity compared with the intestinal contents, which was consistent with previous studies on wild tilapia [ 32 ], finless porpoises [ 36 ], and Rhabdophis subminiatus [ 39 ]. An explanation may be ascribed to feeding behavior, in which the diet has a high microbial diversity due to its exposure to the water environment containing diverse microorganisms [ 42 ], thus resulting in a high microbial diversity in the stomach digesta.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the observed similarities in microbial community composition among aquatic reptiles, both mouth and gut samples of the terrestrial snakes (T. flavomaculatus, B. dendrophila) showed interesting compositional patterns, with both species dominated by Proteobacteria (Figure 1), a phylum observed at much lower relative abundance in most L. laticaudata marine samples, particularly gut samples (Figure 1). Additionally, one dominant phylum, Planctomycetes, was observed exclusively in the mouth samples of B. dendrophila (Figure 1) but has also been observed previously in small relative abundances associated with the GIT of red-necked keelback snakes (Rhabdophis subminiatus; Tang et al, 2019), Galápagos land iguanas (Conolophus subscristatus; Hong et al, 2011), and Santa Fe land iguanas (C. pallidus; Hong et al, 2011). Together these findings reveal new insights into bacterial phyla that may be associated with reptiles that occupy marine vs. terrestrial habitats differentially, presenting exciting directions for future research.…”
Section: Microbial Community Composition Across Host Species and Ecolsupporting
confidence: 81%
“…The present ndings con rm that various effect factors on the microbial diversity resulting from alimentary habits, photoperiod, season, age, elevation and region (Feng et al 2019). In contrast, microbial community and their metabolites were all effective to host, and they participated in nutrient digestion, absorption and metabolic function (Tang et al 2019;Zhang et al 2018), other researchers have found that the diversity and stability of intestinal microbial affected host immune function (Liu et al 2019;Willson et al 2018).…”
Section: Introductionsupporting
confidence: 73%